Handbook of occupational therapy for adults with physical disabilities - Sit, William; Neville, Marsha (Thorofare, NJ : Slack Incorporated, 2020)
Handbook of Occupational Therapy for Adults With Physical Disabilities by Drs. William Sit and Marsha Neville provides quick and essential information for occupational therapists that are new to the adult practice setting.--
Occupational performance -- Central nervous system -- Sensory system, cranial nerves, and peripheral nervous system -- Musculoskeletal system -- Cardiovascular, lymphatic, respiratory, and integumentary systems -- Endocrine, digestive, urinary, and reproductive systems.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
WorldCat record variable field(s) change: 650
Keywords: Occupational therapy -- Handbooks, manuals, etc; People with disabilities -- Rehabilitation -- Handbooks, manuals, etc; Occupational therapy; Adulthood; Occupational Therapy; Disabled Persons -- rehabilitation; Adult; Adultes; occupational therapy; Occupational therapy; People with disabilities -- Rehabilitation; Handbook; Guides et manuels